The Effect of Organic Synthetic Tanning Agents with Different Triazine Structures on Microbial Community Structure in Wastewater - Chuyu SONG; Xihuai QIANG; Xuechuan WANG; Taotao QIANG; Chengtao LI (Pige Kexue Yu Gongcheng)
To explore the environmental impact exerted by triazine-based non-metallic organic synthetic tanning agents, four synthetic tanning agents, namely 1#, 2#, 3# and 5#, were taken as the research subjects. The wastewater samples with the addition of these four synthetic tanning agents were denoted as T1, T2, T3, and T5. The biodegradation performance of the synthetic tanning agents was determined by adopting the BOD5/COD evaluation index and the CO2 evaluation index methods. The influence of the four synthetic tanning agents on the microbial community structure characteristics and microbial ecology in the wastewater was investigated by utilizing high-throughput sequencing technology. The results indicated that all the four non-metallic organic synthetic tanning agents belonged to biodegradable substances. In the wastewater samples of T1, T2, and T3, Firmicutes was the dominant phylum, while Proteobacteria was the dominant phylum in the wastewater sample of T5. Additionally, the triazine structure of the synthetic tanning agents could exert a certain influence on the microbial abundance in the wastewater. The research outcomes provide a reference for the ecological evaluation of triazine-based organic tanning agents and hold significant importance for subsequent studies related to such synthetic tanning agents.